Iodine-based nutrient application improves growth, economic yield and agronomic efficiency in tomato - Babanjeet; Jagdish, S; Kulbir, S; Salesh Kumar, J; Monisha, T; Dilpreet, T (Plant Science Today, 2026)
Tomato (Solanum lycopersicum L.) is one of the most economical vegetable crop worldwide, often limited by nutrient imbalances and suboptimal management practices. This study evaluated the effect of different iodine sources potassium iodide (KI) and potassium iodate (KIO₃) and application methods (seed priming, soil application and foliar spray) on the growth, phenology and yield of tomato over 2 consecutive years. The experiment comprised 9 treatments laid out in a randomized complete block design (RCBD). The central hypothesis proposed that iodine though not traditionally essential but can enhance photosynthetic performance, flowering efficiency and nutrient-use efficiency. Results revealed that iodine application significantly improved plant height, canopy width and number of branches per plant with the highest values observed under the combined application of KI through seed priming, soil and foliar spray (T8). Foliar applications alone in treatments T4 and T5 also performed effectively and promoted early flowering. Yield parameters including total and marketable yield were significantly enhanced by iodine treatments, with T4 (KI foliar spray) depicting increased total yield by 6.5 % and marketable yield by 7 % over the control. The highest benefit-cost ratio (2.80) was recorded in T4 (KI foliar), indicating superior economic efficiency. The positive responses are attributed to iodine's role in enhancing photosynthetic activity, antioxidant defence and hormonal regulation. While integrated application provided maximum physiological benefits, foliar spray alone emerged as the most practical and cost-effective strategy for field conditions. The study suggested that foliar application of KI at 0.01 % offers a sustainable, cost-effective approach to improve vegetative growth, reproductive efficiency and yield in tomato. This approach offers business potential and precision nutrient management and value-added vegetable production worldwide. Future studies should explore its incorporation with digital nutrient mapping and broader vegetable systems for climate-resilient agriculture.